Rancang Bangun Sistem Informasi Penggajian Guru dan Pegawai di SMA Yadika Cicalengka - Viola Elza Billa; Encep Supriatna (Ma'soem University, 2023)
Yadika Cicalengka High School is one of the educational institutions. The payroll management system for teachers and employees at SMA Yadika Cicalengka is still semi-computerized, so it is necessary to have a new computer-based information system that can facilitate payroll management. The development method used in the design of this payroll information system, namely System Development (SDLC) or system life cycle, is a pattern taken to develop a software system with a waterfall model. By using several design tools including Data Flow Diagrams, Chart Structures, Flowmaps, and E-R Diagrams. The development of this information system uses Microsoft Visual Foxpro 9.0 programming language and is divided into three modules, namely master, transaction, report. The design of this information system is made as a solution to the above problems to facilitate the information system. Because the design of this system will improve the performance of the treasurer in payroll management.